Bottoms up and the devil laughs : a journey through the deep state - Howley, Kerry (Alfred A. Knopf, 2023)
"Who are you? You are data about data. You are a map of connections--a culmination of everything you have ever posted, searched, emailed, liked, and followed. In this groundbreaking work of narrative nonfiction, Kerry Howley investigates the curious implications of living in the age of the indelible. Howley's subjects face a challenge new to history: they are imprisoned by their past selves, trapped for as long as the Internet endures. A soap opera set in the deep state, Bottoms Up and the Devil Laughs is a free fall into a world where everything is recorded and nothing is sacred, from a singular writer unafraid to ask essential questions about the strangeness of modern life"--